TRENDS OF THE BOOK SCIENCE DEVELOPMENT IN WESTERN EUROPE IN THE 17TH–18ᵀᴴ CENTURIES - LELIKOVA, NATALIJA (Knygotyra, 2010)
In bibliology, the methodology of historical studies entirely depends on an applied approach. The author adheres to the historical approach that says that a science development is traced with a kind of its historical logic, with all ways of its development, including those that are dead-end. Based on such approach and starting from G. Peignot’s concept of bibliology, the Abstractauthor logically traces trends of bibliology development in Western Europe beginning from the 17th century. The author concludes that by the beginning of the 19th century when Peignot presented his works, in the science there had already been the established corpora of scientific knowledge used by this outstanding French bibliologist.